Fluorescence quenching studies of matrix metalloproteinases (MMPs): evidence for structural rearrangement of the proMMP-2/TIMP-2 complex upon mercurial activation. - Stack, MS; Itoh, Y; Young, T; Nagase, H (1996)
Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases which are secreted from cells as zymogens and can be activated by treatment with organomercurial reagents or limited proteolysis. The proenzyme forms of MMP-2 (gelatinase A) and MMP-9 (gelatinase B) are found in complex with tissue inhibitor of metalloproteinases (designated proMMP-2/ TIMP-2 and proMMP-9/TIMP-1, respectively). The proposed mechanism of activation by mercurial compounds involves the induction of a conformational change in the zymogen which leads to propeptide autoprocessing. To investigate the possibility of conformational differences in MMPs, solute quenching of MMP intrinsic fluorescence was used to probe the relative exposure of tryptophan residues in latent and mercurial-activated MMPs. Our data demonstrate that fluorescence quenching of the proMMP-2/TIMP-2 complex by either acrylamide or iodide is significantly increased following mercurial activation. In contrast, no significant change in tryptophan accessibility accompanies mercurial treatment of either proMMP-2 or TIMP-2 alone, or mercurial-activated MMP-2 mixed with TIMP-2. To determine whether the enhanced fluorescence quenching was unique to the activated proMMP-2/TIMP-2 complex, similar experiments were performed using MMP-1, MMP-3, and MMP-9/TIMP-1 complex. In all cases, both latent and mercurialtreated MMPs exhibited similar fluorescence quenching profiles, suggesting that there are no significant conformational differences between the zymogen and activated forms of MMP-1, -2, -3, or -9/TIMP-1. The enhanced fluorescence quenching observed with mercurial-treated proMMP-2/TIMP-2 is indicative of increased exposure of a previously buried tryptophan residue(s), providing evidence for a structural rearrangement of the activated complex. These data, together with our previous biochemical observation that mercurial treatment of proMMP-2/TIMP-2 exposes the MMP-2 active site without propeptide processing (Y. Itoh et al. (1995) Biochem. J. 308, 645-651), suggest that the activated proMMP-2 in the complex may represent a transitional conformational intermediate in MMP activation.